An Analysis of Wrist Motions During Daily Activities From a Directional Perspective: The Significance of Directions Beyond the Dart‐Throwing Motion - Qipei Wei; Shijie Jia; Shengfang Zhang; Xiaofeng Qiao; Zhixin Wang; Chang Liu; Shanlin Chen (Orthopaedic Surgery)
ABSTRACT Background Previous studies on Activities of Daily Living (ADL) suggest that the wrist demonstrates different ranges of motion and frequencies in various directions. However, the specific directional characteristics of wrist activities remain unexplored. This study aims to investigate the directional characteristics of wrist motions during ADL with optical motion capture technology. Method This is a basic science study. Twenty‐six right‐handed subjects executed 22 ADLs, with angular wrist positions tracked via retroreflective markers on the dominant limb. The Cartesian coordinate system formed by wrist flexion–extension and radial–ulnar deviation angles was transformed into a polar coordinate system, enabling the directional analysis and the calculation of the directional range of motion (ROM). The directional distribution of trajectory points was analyzed using the Rayleigh test and visualized. The values and trends of directional RoM in 72 directions for both aggregated and individual ADLs were examined. The peaks of ROMs across ADLs were clustered using K‐means to identify key directions. Differences in gender and age were analyzed with a two‐way ANOVA. Result The trajectories exhibited a strong directional preference across all ADLs (p < 0.01). In the majority of ADLs, the trajectories favored the ulnar extension direction (19/22) and were distributed along the radial flexion–ulnar extension plane (12/22). ROM was calculated for each of the 72 directions in each ADL. The aggregated ADL analysis provided the directional functional ROM (fROM). Three types of ADLs were identified, each with 1, 2, and 3 peaks in their directional ROM, respectively. Three key directions were identified as clusters of peak ROMs in the ADLs. Comparisons across gender and age groups revealed varying preferences for directional ROM in each group. Conclusion This study identified three key wrist motion directions essential for daily functions, highlighting the critical role of ulnar extension. Additionally, it demonstrated variations in directional wrist motion preferences across different genders and age groups.